Legitimasi Politik dan Representasi Moral dalam Debat Pemilihan Gubernur DKI Jakarta 2017 : Political Legitimacy and Moral Representation in the 2017 Jakarta Gubernatorial Debate: A Critical Metaphor Analysis - Aliurridha Aliurridha; Mustakim Saleh (Transformatika: Jurnal Bahasa, Sastra, dan Pengajarannya, 2026)
This study examines how metaphors are used as mechanisms of political legitimacy in the 2017 Jakarta Gubernatorial Debate. The study departs from the view that metaphors in political discourse can function as discursive strategies that construct moral representation, legitimize power, and shape the relationship between leaders and the people. By integrating Conceptual Metaphor Theory and Critical Discourse Analysis, this study seeks to explain the ideological functions of metaphor in Indonesian political discourse. The data consist of metaphorical expressions found in the debates between the Ahok–Djarot and Anies–Sandi candidate pairs. The findings show that metaphors are employed to construct moral legitimacy through representations of leadership, social justice, public welfare, and the delegitimization of political opponents. Metaphors also play a significant role in shaping moral frameworks that determine how political actions are understood as rational, moral, and worthy of public support within contemporary Indonesian democratic discourse.